Communication and Disaster Education in The Perspective of Learning Theory: A Literature Review - Ode Sitti Nurhaliza, Wa; Yasya, Wichitra; Ayuningtyas, Qurota (Siber Journal of Advanced Multidisciplinary, 2024)
Indonesia is known as a supermarket disaster country. Responding to various disasters that have occurred, and even potential disasters, has prompted various parties to take concrete steps as disaster mitigation efforts. Communication plays a crucial role in disaster information flow. Communicators, in this case, the National Disaster Management Agency (BNPB) and authorized parties, are key to the smooth dissemination of disaster messages/information. However, the community, as the affected party in disasters, also needs to be provided with clear information on how to deal with disaster situations. This article aims to identify and explain the application of learning theories in the context of disaster communication, describe the development of disaster communication research in Indonesia, and discuss the implementation of disaster education concepts in various countries. The method used is a literature review from related ebooks and journals. The results obtained are as follows: First, communication and disaster education are interrelated in order to enhance disaster literacy across all regions. Second, communication plays a primary role in disaster education programs from the government's policy-making perspective, institutions observing disaster issues, and the community (disaster victims). Effective, efficient, and targeted information flow is crucial both in pre-disaster, during a disaster, and post-disaster phases. Third, there is a need to integrate disaster education into the curriculum, both at the school and university levels. This ensures that each individual knows and understands what to do when a disaster occurs, how we perceive disasters, and so on. Additionally, various theoretical approaches can be used to study disaster communication in an educational context, including: Behavioral learning, which focuses on observable behaviors, Cognitive Learning, which views learning as a mental process, Affective learning, which is related to emotions and affection and plays a role in learning, and Social learning, which views disaster learning as a social process where knowledge is collectively built within a specific social environment.